THE ROLE OF PLEKSIBILITY IN EDUCATIONAL INNOVATION - Tengku Darmansah (Universitas Dharmawangsa Medan, 2020)
Innovation is an idea, an item, an event, a method that is perceived orobserved as a new thing for a person or group of people (society), whetherit is the results of invention and discoveri. Innovations are held to achievea specific goal or to solve a particular problem. Versatility (Flexibility) isthe ability to adapt and work effectively in different situations, and withdifferent individuals or groups. Flexibility requires the ability tounderstand and appreciate different and conflicting views on an issue,adjusting its approach due to a change of situation, and can easily receivechanges in its organization.